The tracing of mycobacteria in drinking water supply systems by culture, conventional, and real time PCRs - Klanicova, Barbora; Seda, Jaromir; Slana, Iva; Slany, Michal; Pavlik, Ivo (Current microbiology, 2013)
Mycobacteria are widely present in diverse aquatic habitats, where they can survive for months or years while some species can even proliferate. The resistance of different mycobacterial species to disinfection methods like chlorination or ozonation could result in their presence in the final tap water of consumers. In this study, the culture method, Mycobacterium tuberculosis complex conventional duplex PCR for detection of non-tuberculous mycobacteria (NTM) and quantitative real-time PCR (qPCR) to detect three subspecies of M. avium species (M. a. avium, M. a. hominissuis, and M. a. paratuberculosis) were used to trace their possible path of transmission from the watershed through the reservoir and drinking water plant to raw drinking water and finally to households. A total of 124 samples from four drinking water supply systems in the Czech Republic, 52 dam sediments, 34 water treatment plant sludge samples, and 38 tap water household sediments, were analyzed. NTM of 11 different species were isolated by culture from 42 (33.9 %) samples; the most prevalent were M. gordonae (16.7 %), M. triplex (14.3 %), M. lentiflavum (9.5 %), M. a. avium (7.1 %), M. montefiorenase (7.1 %), and M. nonchromogenicum (7.1 %). NTM DNA was detected in 92 (76.7 %) samples. By qPCR analysis a statistically significant decrease (P < 0.01) was observed along the route from the reservoir (dam sediments), through water treatment sludge and finally to household sediments. The concentrations ranged from 10(0) to 10(4) DNA cells/g. It was confirmed that drinking water supply systems (watershed-reservoir-drinking water treatment plant-household) might be a potential transmission route for mycobacteria.
Keywords: Polymerase Chain Reaction; Water Supply; zásobování vodou; Prevalence; netuberkulózní mykobakterie; pitná voda; Bacteriological Techniques; Česká republika; Czech Republic; Nontuberculous Mycobacteria; Drinking Water; bakteriologické techniky; polymerázová řetězová reakce; prevalence